A retrospective observational study of neuromuscular monitoring practice in 30, 430 cases from six Danish hospitals. (15th May 2020) - Thomsen, J. L. D.; Staehr‐Rye, A. K.; Mathiesen, O.; Hägi‐Pedersen, D.; Gätke, M. R.
Summary: Timely application of objective neuromuscular monitoring can avoid residual neuromuscular blockade. We assessed the frequency of objective neuromuscular monitoring with acceleromyography and the last recorded train‐of‐four ratio in a cohort of Danish patients. We extracted data from all patients receiving general anaesthesia from November 2014 to November 2016 at six hospitals in the Zealand Region of Denmark. Acceleromyography was available in all operating rooms and data were recorded automatically. The primary outcome measure was acceleromyography use in patients receiving neuromuscular blocking agents, divided into non‐depolarising agents and succinylcholine only. The dataset included 76, 743 cases, of which 30, 430 received a neuromuscular blocking drug. Non‐depolarising drugs were used in 16, 525 (54%) and succinylcholine as the sole drug in 13, 905 (46%) cases. Acceleromyography was used in 14, 463 (88%) patients who received a non‐depolarising neuromuscular blocking drug and in 4224 (30%) receiving succinylcholine alone. Acceleromyography use varied between the departments from 58% to 99% for non‐depolarising drugs and from 3% to 79% for succinylcholine alone. The median (IQR [range]) of the last recorded train‐of‐four ratio before tracheal extubation was 0.97 (0.90–1.06 [0.01–2.20]) when non‐depolarising drugs were used, and was less than 0.9 in 22% of cases. The OR for oxygen desaturation was higher with the use of succinylcholine [2.51 (95%CI 2.33–2.70) p < 0.001] and non‐depolarising drugs [2.57 (95%CI 2.32–2.84) p < 0.001] as compared with cases where no neuromuscular blockade drug was used. In conclusion, acceleromyography was almost always used in cases where non‐depolarising neuromuscular blocking drugs were used, but a train‐of‐four ratio of 0.9 was not always achieved. Monitoring was used in less than 30% of cases where succinylcholine was the sole drug used.